Despacho econômico multiárea descentralizado considerando a participação de agregadores privados locais usando o método meta-heurístico - Adeyanju, Olatunji Matthew (2022)
The power systems operation has been mostly based on centralized solutions. In the recent time however, the power system economic models are changing because of the inclusion of new private participants in the system and policies that support 100 percent renewable energy (RE) integration. This new paradigm increases the power systems complexity considering the autonomy of the individual participants. Non transparency in data exchange among operators also limits the effectiveness of the centralized solutions, making centralized operation more challenging. As a result, the motivation to develop decentralized solution that allows individual operator to effectively manage its operation while interacting with other operators becomes necessary for secure and reliable operations of the entire grid. Furthermore, the classical multiarea operation problem has been studied by many authors using some conventional piece-wise linearized mathematical methods. Alternatively, where there is need to address complex and non-convex functions, the metaheuristic methods are considered suitable. However, despite this capability, the existing metaheuristic methods have been limited to either using centralized models or not considering multiple autonomous participants in their decision-making frameworks. Consequently, this research develops two novels decentralized multiarea economic dispatch models based on metaheuristic optimization (MO) to manage the operation of some transmission system operators (TSOs) and private aggregators (PAs) of RE resources including battery storages in an interconnected multiarea power systems context. The first model is a semi-decentralized (SD) model developed to attract wider inclusion of PAs in the transmission systems by allowing them to maximize profits. The second model is a fully decentralized (FD) model developed to coordinate the operation the PAs with the TSOs to preserve their baselines. The proposed models allow to determine the effective integration of autonomous PAs in the transmission systems (TS) and their co-operation with the TSOs. The objective of both models is to minimize the total operation cost of the system by effectively coordinating the TSOs and PAs operations. The TSOs and PAs evaluate their operational uncertainties and determine the power reserves considering the best and worst-case scenarios of the uncertain variables, thus enabling the resulting models to be solved in three stages using select metaheuristic methods (MM). To preserve the ownership of TSOs and PAs, the MM efficiently utilizes separate population sets to solve the operations of the areas in parallel in a two-layer operation approach, allowing the TSOs and PAs to achieve near-optimal operations, independently. Case studies are performed on a modified Nigerian 330 kV 39-bus transmission systems having three TSOs each with three PAs to demonstrate the effectiveness of the proposed models. The simulation results obtained showed the performance superiority of the novel models over their centralized counterpart model.